Satisfaction on the use of mobility aids among lower limb amputees and impact on activities of daily living in Selangor, Malaysia - Yunos, Nurulizzatie; Hamzah, Siti Aishah; Romli, Muhammad Hibatullah; Makhdzir, Norafisyah; Aris, Aishairma (International Islamic University Malaysia Press, 2021)
Introduction: This study aims to determine the level of satisfaction on the mobility aids the dependence in activities of daily living among amputees in Bangi, Selangor. Methods: The data was collected at Pusat Latihan Perindustrian dan Pemulihan (PLPP), Bangi in Selangor, Malaysia, on 55 lower-limb amputees using a cross-sectional design. An instrument used was adapted from Quebec User Evaluation of Satisfaction with assistive Technology (QUEST 2.0) and Barthel Index (BI). These two instruments were combined to evaluate the satisfaction of assistive aids used and dependence of activities daily living. Results: Total mean score of level of satisfaction was 3.99 (95%CI=3.85–4.13) and level of dependence was 85.00 (95%CI=81.28–88.72). The Kruskal-Wallis test was conducted to evaluate the association of mobility aids used with level of satisfaction and level of dependence. The results showed there was no significant association between mobility aids used and level of satisfaction. Meanwhile there was a significant association between mobility aids used and dependence (p=0.001). Multiple linear regression test showed the combination of mobility aids used and level of satisfaction was found significantly associated with the level of dependency (p=0.024). The final analysis, when only mobility aids used was included as a single variable (without the combination with the level of satisfaction), it was found statistically associated with the level of independence while the level of satisfaction score is excluded. Conclusion: Mobility aids used was found no significant association with the level of satisfaction however, user who used cast prosthesis as mobility aids found prothesis provided them more dependency in performing activities daily living. Despite prothesis was found as the most convenience mobility aid, users did not see it as something that can give them satisfaction. This could be because of the mobility aids that provide dependency are not cost-effective. It is recommended that users can get more options to use mobility aids that can provide them dependency, nevertheless the mobility aids must be affordable for them.